Current trends in the emotional and social aspects of the school readiness research - Urszula Oszwa (Ignatianum University Press, 2018)
The school readiness issues have been being in the focus of interests of the educators for years. The number of approaches, tendencies and dimensions of the school readiness indicates how comprehensive and complex this topic is. The analysis of the contemporary research directions based on the papers available in academic databases let arrange them into a few categories. They are all presented in the article with the aim to get the current perspective of the problem, especially in the social and emotional context. Some authors try to determine the list of the detailed aspects of emotional and social skills important to begin school education. The other approach presents the new school readiness tools. There is also a line that evaluates the early emotional support effect on school readiness. The next trend is formed by statistical meta-analyses on the correlation between the age of the school start and pupils achievements. The two new directions are related to the school readiness profiles and the idea to include the executive functions into school readiness assessment as an important aspect of pupils' emotional and social achievements. The results coming from those six directions help the educators to increase the early education care.